Prevalence of and factors associated with depression, anxiety, and stress among first year undergraduate students in a Malaysian Public University - Hassan, Mohammed (2016)
Depression, anxiety and stress are the most reported and studied forms of mental illnesses among adolescence and young adults in Malaysia, and their burden seems to be on the increase. Reasons for the increase apart from the inconspicuous nature of their signs and symptoms maybe, due to lack of awareness of physical and psychological symptoms associated with these conditions also, fear of stigmatization. Previous studies have primarily focused on medical students, however, these psychological problems may extend to other students regardless of field of study. The purpose of this study is to determine the prevalence of and factors associated with depression, anxiety and stress among first year undergraduates in a Malaysian public university. A cross-sectional study was conducted in UPM Serdang campus among 675 first year undergraduate students from the Faculties of Agriculture, Design and Architecture, Education, Environmental studies and Medicine and Health sciences. Cluster sampling method was used to collect information on socio demographic, socio economic, environmental factors, through the use of validated selfadministered questionnaires between November 2014 and May 2015. Data was analyzed using, descriptive, bivariate and multivariate data analysis by SPSS™ (version 21). The test used were Chi-square test, Independent t-test, Mann-Whitney U test, Logistic regression and Multiple logistic regression. The study response rate was 78.5%. The prevalence of depression, anxiety and stress was 32.1%, 64.6% and 29.2% respectively. The majority of respondents were, females (71.1%), Malays (81.5%), Muslims (84.4%), in the Faculty of Medicine and Health Sciences (30.2%), resided in dormitories (99.1%) and between ages 18-25 years. The majority parents had secondary education (40.9%) and worked in the government sector (26.6%). Majority of father‘s earned a monthly income less than RM2500 (61.3%) and, the majority of mothers earned no monthly income (59.4%). The independent factors of depression included ages of 20-21 years (AOR= 0.545, 95% CI 0.312 – 0.952), parent's education (AOR= 2.496, 95% CI 1.458 – 4.276), negative automatic thoughts (AOR= 2.021, 95% CI 1.250 – 3.270) and substance use (AOR= 1.374, 95% CI 1.200 – 1.574). Predictors of anxiety were, female (AOR= 1.619, 95% CI 1.132–2.316), parents education (AOR= 2.274, 95% CI 1.240 – 4.168), attachment to mother (AOR= 0.988, 95% CI 0.978 – 0.998) and behavioral disengagement (AOR= 1.183, 95% CI 1.064 – 1.318)While, predictors of stress were mother‘s income (AOR= 1.711, 95% CI 1.195 – 2.450), negative automatic thoughts (AOR= 2.108, 95% CI 1.253 – 3.547), attachment to mother (AOR= 0.986, 95% CI 0.976 -0.997) and venting (AOR= 1.190, 95% CI 1.062 – 1.338). In conclusion, the prevalence of depression, anxiety and stress were high among all study groups and the majority of associated factors were modifiable. It is paramount that attention is given and intervention strategies, screening and creating more awareness as this may help to effect early preventive measures among students.